Brain Edema XV - Katayama, Yoichi; Maeda, Takeshi; Kuroiwa, Toshihiko (Acta neurochirurgica, 2013)
More than 60 papers written by internationally recognized experts cover the broad spectrum of brain edema. The main topics treated are: ischemia hemorrhage, trauma (experimental and clinical), cerebral hemorrhage, tumor, hydrocephlaus intracranial pressure (ICP), neuromonitoring neuroimaging, treatments, blood brain barrier, and miscellaneous.
Keywords: Konferenzschrift